Asociación entre funcionamiento familiar y calidad de vida en familias con un hijo con asma - Núñez Tapia, Rosa María (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The medicine of first level of attention has like ideal the prevention of the diseases, as well as to evaluate the surroundings of the patient, this with the purpose of to give to direction and support to the family of the patient in this case of the boy with asthma, since it has increased to his prevalence in the last years; getting to worry to the parents as much about the minors who suffer like the doctor to their position. Objective: the present study has like objective evaluating if it exists association between familiar operation and the quality of life of the asthmatic boy and its caretaker. Material and Methods: In order to evaluate and to consider the association degree instruments like PAQLQ and PACQLQ were used, that evaluate quality of life of the boy with asthma and the one of their caretaker; and FF-SIL that evaluates the degree of familiar dysfunction, evaluating later the association among them, all this with the consent informed into the caretakers of the minor. Results: 50 paediatric patients with asthma studied, of which 54% belonged to the femenine and 46% of the masculine. The participants of the study who counted on an age of 7 to 10 years at the time of the application of the instrument were 62%, in the same way 36% told on an age of 11 15 years; 64% of the studied families were nuclear, who counted on a moderate functionality according to FF-SIL, 10% were dysfunctional, and 26% were functional. When considering the force of the association between limitation of activities of the boy and limitation of the parents calculated a coefficient of determination R2= 0,351 which implies a force of low association to average.

La medicina de primer nivel de atención tiene como ideal la prevención de las enfermedades, así como evaluar el entorno del paciente, esto con el fin de dar orientación y apoyo a la familia del paciente en este caso del niño con asma, ya que ha aumentado su prevalencia en los últimos años; llegando a preocupar tanto a los padres de los menores que la padecen como al médico a su cargo. Objetivo: el presente estudio tiene como objetivo el evaluar si existe asociación entre funcionamiento familiar y la calidad de vida del niño asmático y su cuidador. Material y Métodos: Para evaluar y estimar el grado de asociación se utilizaron instrumentos como PAQLQ y PACQLQ, que evalúan calidad de vida del niño con asma y la de su cuidador; y FF-SIL que evalúa el grado de disfunción familiar, evaluando posteriormente la asociación entre ellos, todo esto con el consentimiento informado de los cuidadores del menor. Resultados: Se estudiaron 50 pacientes pediátricos con asma, de los cuales el 54% pertenecieron al género femenino y el 46% del género masculino. Los participantes del estudio que contaban con una edad de 7 a 10 años al momento de la aplicación del instrumento fueron el 62%, del mismo modo el 36% contaba con una edad de 11 a 15 años; el 64% de las familias estudiadas fueron nucleares, las cuales contaron con una moderada funcionalidad según FF-SIL, el 10% fueron disfuncionales, y el 26% fueron funcionales. Al estimar la fuerza de la asociación entre limitación de actividades del niño y limitación de los padres se calculó un coeficiente de determinación R2= 0.351 lo cual implica una fuerza de asociación baja a media.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4135; info:eu-repo/classification/cti/3; FCMB-E-2010-0035; Calidad de vida; Funcionamiento familiar; Cuidador